So you want to be an inventor? - St. George, Judith, 1931-; Small, David, 1945- (New York : Philomel Books, 2002)
Presents some of the characteristics of inventors by describing the inventions of people such as Alexander Graham Bell, Thomas Edison, and Eli Whitney.
Includes bibliographical references (p. 52).
6.0
3-6
Keywords: Inventions -- Juvenile literature; Children as inventors -- Juvenile literature; Inventors; Inventions; Inventors; Inventions